Economics of fish farming in Tripura - Debnath, Chandan; Sahoo, Lopamudra; Debnath, Biswajit; Das, S. K.; Ngachan, S. V. (Indian Journal of Hill Farming, 2018)
Fisheries occupy a unique place in the economy and livelihood of Tripura. More than 95% people of Tripura are eating fish as an important source of protein. Fish here is a high-valued commodity and models of fish farming are highly dynamic. There is no systematic approach to account the profitability of fish farming. Unless the economics and scale of economy of farming are assessed, fisheries will not sustain. In this paper, the economics of nursing, rearing and culture Indian major carps in a kani of pond (0.16 ha) were assessed. Net profit obtained was Rs. 27,680/- in nursery phase, Rs. 16,110/- in rearing phase and Rs. 54,250/- in grow-out phase. Benefit cost ratio was highest in nursery (1.85), followed by in culture (1.82) and rearing phase (1.40). This suggests for opting fish farming as profitable livelihood enterprise.